Re-designing reference services a case study for 21st century learning - Eclevia, Marian Ramos (PLAI Journal, 2016)
With its strong commitment to creating a better and higher level of user experience, the De La Salle University (DLSU) Libraries has reinvented, redesigned and redefined its reference services and programs through the implementation of several tools namely: IamInfoSMART for information literacy campaign; the League of Information Assistants (LIA), the virtual subject librarians; the Roving Information Assistants (RIAs), the point of need reference librarians; and the Face-to-Face with RIA, for booking a librarian to cater to the patron's needs for 24/7 online help as well as for a intensive and personalized, face-to-face instruction. Commenced in November 2013, these services and programs have resulted to a better customer service, librarian/student engagement, and collaboration with its partners in the academic community. This case study discusses the design, development, and implementation of the current reference services and programs of the DLSU Libraries that responded to changes related to increased online instructions via Chat with LORA (Library Online Reference Assistant), shifting usage pattern, and student learning behaviors. It also investigates the students' confidence in a number of areas of information literacy, their instruction preferences as they learn to become lifelong learners, and their perceived characteristics of online self-paced information literacy module. This study is based on interviews with a team of librarians who conceptualized and developed the IamInfoSMART campaign, LIA and RIA. Survey questionnaires were also distributed to measure the level of information literary skills of undergraduate students, determine their reasons for attending information literacy sessions, and identify their expectations with library online tutorials.